Inserção da iniciação científica em nível escolar na base da pirâmide de formação acadêmica universitária: um sistema multivetorial de educação em ciência e tecnologia. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Brazil's low indices in the performance of students of basic education in international assessments, demonstrates the need to invest in ways to reduce this gap, especially in science education. In this perspective, there is a need for the interconnection between the university and the basic school as a priority for scientific and technological development and also as an education model capable of improving such alarming rates. In this perspective, the scientific initiation emerged as a possibility to approach and strengthen the relations between the university and the basic school, allowing a real interface between these two realities. Taking into account such needs, the Interdisciplinary Action Program (PAI) was created as an interlocution program between the University and the School, committed to resolve the distances between the two realities and guarantee full dissemination of academic thinking as a propulsion of the teaching qualification. The objective of this study is to study the effects of integrated scholarly scientific initiation in the pyramid of university education as a function of improving learning. As a methodological strategy, we used a follow-up questionnaire applied to the students participating in the program in 2010, followed by an online questionnaire applied to the graduates of the same period (Phase 1 evaluation), and the third and final stage consisted of a comparative research of school performance and the National High School Examination (ENEM) among students participating in the Program and students who were eligible to join the EPI, but did not participate (Phase 2 Assessment). The results showed that the student exposed to the method acquires autonomous behavior in the teaching learning relationship, providing a more effective intellectual development than the other students of the public school network, including the acquisition of language mastery and interpersonal communication. In general, these evaluations point to an effective contribution of this method to the improvement of crucial elements for the teaching-learning relationship, scientific literacy, logical criticism, reading and writing skills, and greater attention of the family to the intellectual development of its students.
Keywords: Ciências Biológicas; Iniciação científica; Educação básica; Programa de Ação Interdisciplinar; Ensino-aprendizagem; CNPQ::CIÊNCIAS BIOLÓGICAS; CIÊNCIAS BIOLÓGICAS